Measuring the Competitiveness of Ciamis Regency Using Location Quotient and Shift Share Analysis - Amalia, Lidya Nur (Universitas Galuh, 2025)
Increased economic growth shows that economic activity in a region is running well. The economic capabilities of each region are different, so this research was conducted with the aim of analyzing the competitiveness of the economic sectors in Ciamis Regency. This research uses secondary data obtained from the Central Statistics Agency for West Java Province and Ciamis Regency in 2020-2023. The analysis used in this research is location quotient analysis and shift share analysis. The research results of statistic location quotient and dynamic location quotient combination shows that the sectors included in the basic and prospective sectors are the agriculture, forestry, and fisheries sectors, construction, education services, warehousing transportation, provision of accommodation and food and beverages, and the information and communication sector, while the results of the shift share analysis show that the sectors that are growing rapidly and have competitiveness are the real estate sector, corporate services, health services and social activities, and other services.